An Activity-Based Proteomics with Two-Dimensional Polyacrylamide Gel Electrophoresis (2D-PAGE) for Identifying Target Proteases in Arabidopsis Apoplastic Fluid - Sayaka Matsui; Yoshikatsu Matsubayashi (Bio-Protocol)
Plant proteases participate in a wide variety of biological processes, including development, growth, and defense. To date, numerous proteases have been functionally identified through genetic studies. However, redundancy among certain proteases can obscure their roles, as single-gene loss-of-function mutants often exhibit no discernible phenotype, limiting identification through genetic approaches. Here, we describe an efficient system for the identification of target proteases that cleave specific substrates in the Arabidopsis apoplastic fluid. The method involves using Arabidopsis-submerged culture medium, which contains apoplastic proteases, followed by native two-dimensional electrophoresis. Gel fractionation and an in-gel peptide cleavage assay with a fluorescence-quenching peptide substrate are then used to detect specific proteolytic activity. The active fraction is then subjected to mass spectrometry–based proteomics to identify the protease of interest. This method allows for the efficient and comprehensive identification of proteases with specific substrate cleavage activities in the apoplast.